A Design Method for Time Sequential Synchronization of Semi-Physical Simulation on Guidance Weapon System - Li, Da Wei; Cui, Liu Zheng; Jiang, Rui Kai (Applied Mechanics and Materials, 2013)
To solve the problem of the time sequential synchronization of semi-physical simulation on some guidance weapon system, we proposed a method of zero time alignment and simulation time adjustment. The simulation results indicate the strategy of synchronization is feasible, and the time sequential of the semi-physical simulation is correct.